A full-scale fluvial flood modelling framework based on a high-performance integrated hydrodynamic modelling system (HiPIMS) - Xia, Xilin; Liang, Qiuhua; Ming, Xiaodong (Advances in water resources, 2019)
•A full-scale fluvial flood modelling framework based on a high-performance hydrodynamic model solving the 2D SWEs.•Successful application to reproduce a storm induced flood in a 2500 km2 catchment at 5 m resolution.•High-resolution grid is essential for accurately simulating large-scale fluvial flood using a 2D hydrodynamic model. Full-scale fluvial flood modelling over large catchments has traditionally been carried out using coupled hydrological and hydraulic/hydrodynamic models. Such a traditional modelling approach is not well suited for the simulation of extreme floods induced by intense rainfall, which is usually featured with highly transient and dynamic rainfall-runoff and flooding process. This work aims to develop and demonstrate a modelling framework to predict the full-scale process of fluvial flooding from the source (rainfall) to impact (inundation) over a large catchment using a single high-performance hydrodynamic model driven by rainfall inputs. The modelling framework is applied to reproduce the flood event caused by the 2015 Storm Desmond in the 2500 km2 Eden Catchment at 5 m resolution. Without intensive model calibration, the predicted results compare well with field observations in terms of inundation extent and gauged water levels across the catchment. Sensitivity tests reveal that high-resolution grid is essential for accurate simulation of fluvial flood events using a 2D hydrodynamic model. Accelerated by multiple modern GPUs, the simulation is more than 2.5 times faster than real time although it involves 100 million computational cells inside the computational domain. This work provides a novel and promising approach to assess and forecast at real time the risk of extreme fluvial floods from intense rainfall.